Analisa Dampak Penerapan Akuntansi Sewa Pembiayaan terhadap Laporan Posisi Keuangan, Laporan Laba Rugi, dan Rasio Solvabilitas: Studi Pada Perusahaan Terbuka di Indonesia - Herry Respati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
IFRS 16 is the latest lease accounting standard to be implemented by PSAK 73 in Indonesia. PSAK 73 regulates the recognition, measurement, presentation, and disclosure of leases for lessees by classifying leases as finance leases. This results in the assets and liabilities from lease transactions being recognized in the financial statements, with optional exceptions for short-term leases and leases with low-value underlying assets. This study aims to evaluate the impact of implementing PSAK 73 on the assessment of company financial performance through financial ratios. The sample consists of nine companies from each of three industrial sectors: manufacturing, mining, and services, which are listed on the Indonesia Stock Exchange in 2020. The method used in this study is the constructive lease capitalization model developed by Imhoff, Lipe, and Wright (1991). The results show that the impact of lease capitalization is most significant in the service industry, followed by the mining and manufacturing industries, with average changes in Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), as well as decreases in Return on Asset (ROA) and Return on Equity (ROE).